High purity tantalum powder and method for preparing same

A novel multi-step process effectively reduces the content of metal impurities in tantalum powders, achieving high purity levels by incorporating grinding, pickling, vacuum heat treatment, and oxygen reduction steps.

JP2025514411APending Publication Date: 2025-05-02NINGXIA ORIENT TANTALUM INDUSTRY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024563943
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2022-09-06
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing methods for producing high purity tantalum powders struggle to effectively reduce the content of high melting point metals like W, Mo, and Nb, as well as magnesium and oxygen, which are difficult to remove through conventional purification processes.

Method used

A multi-step process involving primary and secondary grinding, pickling, vacuum heat treatment, oxygen reduction, and passivation is employed to produce high purity tantalum powders with reduced content of metal impurities, particularly W, Mo, Nb, magnesium, and oxygen.

Benefits of technology

The process achieves a significant reduction in the content of metal impurities, resulting in high purity tantalum powders with total W, Mo, and Nb content below 0.6 ppm, magnesium content below 1 ppm, and oxygen content below 600 ppm, meeting the requirements for high purity tantalum products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514411000001
    Figure 2025514411000001
  • Figure 2025514411000002
    Figure 2025514411000002
  • Figure 2025514411000003
    Figure 2025514411000003
Patent Text Reader

Abstract

High purity tantalum powder and its manufacturing method. The total content of W, Mo, and Nb in the high purity tantalum powder is less than 0.6 ppm, the Mg content is less than 1 ppm, and the oxygen content is less than 600 ppm. The high purity tantalum powder can be used to prepare high purity tantalum targets.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is in the field of metallurgy, and more particularly relates to high purity tantalum powder and a method for producing the same. cross reference This application claims priority to Chinese Patent Application No. 202210466030.6, filed on April 29, 2022, the entire contents of which are incorporated herein by reference. [Background technology]

[0002] Tantalum is an important rare high melting point metal material. It has good heat resistance, corrosion resistance, oxidation resistance, and atomic migration resistance, and is a suitable sputtering target material for the barrier layer of semiconductor chips with integrated circuit line widths of 45 nm or less. The manufacturing method of a high purity tantalum target includes the following steps: melting high purity tantalum powder with an electron beam to obtain a high purity tantalum ingot, and performing thermomechanical processing to obtain a high purity tantalum target.

[0003] In the process of producing high-purity tantalum ingots from high-purity tantalum powder, it is difficult to remove some high-melting point metals such as W, Mo, Nb, etc. Therefore, it is necessary to provide high-purity tantalum powder with a low content of metal impurities. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] U.S. Patent No. 2,950,185 Summary of the Invention [Problem to be solved by the invention]

[0005] Contents of the invention It is difficult to reduce the content of refractory metals (W, Mo, Nb, etc.), magnesium, and oxygen. On the other hand, refractory metals are not easily removed by refining. On the other hand, to obtain tantalum powder with a low oxygen content, it is necessary to carry out an oxygen reduction operation using magnesium powder, but this operation increases the magnesium content in the tantalum powder. [Means for solving the problem]

[0006] In consideration of the above problems, the present invention provides a new type of high purity tantalum powder and its preparation method. The tantalum powder produced by the method of the present application has a significantly reduced content of metal impurities, especially the reduced content of high melting point metals (e.g. W, Mo, Nb), magnesium and oxygen.

[0007] In some embodiments, the present application provides a method for preparing high purity tantalum powder having a total content of W, Mo and Nb of less than 0.6 ppm, a magnesium content of less than 1 ppm, and an oxygen content of less than 600 ppm, the method comprising the steps of: 1) preparing a tantalum raw material powder having a total content of W, Mo and Nb of less than 0.6 ppm; 2) A step of subjecting the tantalum raw material powder to a first pulverization (primary pulverization) to obtain a first pulverized tantalum powder, the bulk density of the first pulverized tantalum powder being greater than 2.6 g / cm3 (for example, 2.6 to 6 g / cm3). 3 , e.g. 2.68g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 , 4g / cm 3 or 5g / cm 3 ); 3) performing a first pickling process (primary pickling) on ​​the first ground tantalum powder to obtain a first pickled tantalum powder; 4) subjecting the first pickled tantalum powder to a vacuum heat treatment, and passivating the tantalum powder after the vacuum heat treatment to obtain a passivated tantalum powder; 5) doping the passivated tantalum powder with a metal reducing agent, performing an oxygen reduction heat treatment, passivating the powder, and discharging the passivated powder out of the furnace to obtain an oxygen-reduced powder; 6) performing a second grinding (secondary grinding) of the oxygen-reduced powder until it can pass through a 5-15 mesh sieve (e.g., a 10 mesh sieve) to obtain a second ground powder; 7) performing a second pickling on the second ground powder to obtain a second pickled tantalum powder; 8) Washing and drying the second pickled tantalum powder.

[0008] In some embodiments, the vacuum heat treatment is performed at 3×10 -3 It is carried out at absolute pressure values ​​below Pa.

[0009] In some embodiments, the sum of the contents of W, Mo, and Nb elements in the tantalum raw material powder is less than 0.6 ppm, such as less than 0.4 mm, such as less than 0.3 mm.

[0010] In the above embodiment, it is important that the sum of the contents of W, Mo, and Nb in the tantalum raw material powder is less than 0.6 ppm, which helps to reduce the contents of W, Mo, and Nb from the source, thereby obtaining a product with low contents of W, Mo, and Nb.

[0011] In the above embodiment, the bulk density of the first crushed tantalum powder is 2.6 g / cm 3 This allows impurities such as W and Mo contained in the tantalum powder particles to be released, which is favorable for further improving the purity in the later stage.

[0012] In the above embodiment, the first pickling is important and serves to remove contaminants such as Fe, Ni, Cr and other impurities from the surface of the tantalum powder and to remove some of the refractory impurities W, Mo, Nb, thereby improving the purity of the product.

[0013] In the above embodiment, the vacuum heat treatment serves to remove a portion of the gas impurities and low-melting-point metal impurities adsorbed during the pickling process, and at the same time, can promote aggregation and sintering of a portion of the particles.

[0014] In the above embodiment, it is important that the second crushed tantalum powder can pass through a 5-15 mesh sieve. Since the oxygen reduction process is a solid-liquid two-phase oxidation-reduction reaction, magnesium acting as a reducing agent is easily incorporated into the tantalum powder, and the magnesium impurities cannot be effectively removed during the subsequent pickling refining, so that the obtained tantalum powder has a high content of metallic magnesium impurities. After careful research, the inventors have found that adding a reasonable crushing process after discharging the powder from the furnace for oxygen reduction treatment can crush the particles and effectively open the tantalum particles containing magnesium wrapped therein, which provides favorable conditions for the subsequent pickling refining to remove metallic magnesium.

[0015] In the above embodiment, the second pickling is important and has the function of removing contaminants such as Fe, Ni, Cr and other impurities from the surface of the tantalum powder, and removing part of the refractory impurities W, Mo, Nb, thereby improving the purity.

[0016] In some embodiments, the apparatus for performing the first grinding operation may be a ball mill, such as a planetary ball mill, a vibrating ball mill, a tumble ball mill, etc. When the grinding apparatus is a ball mill, the ratio of balls to material is, for example, 0.4 to 1:1.

[0017] In some embodiments, the device for performing the second crushing operation may be a jaw crusher, a cone crusher, a counter impact crusher.

[0018] In some embodiments, the method for preparing high purity tantalum powder according to the present application further comprises reducing the tantalum-containing salt with a reducing agent to obtain a tantalum raw material powder.

[0019] The purity of the reducing agent is 99.9% or more.

[0020] The total content of W, Mo and Nb in the tantalum-containing salt is less than 1 ppm. Using a tantalum-containing salt with a total content of W, Mo and Nb of less than 1.0 ppm as raw material is advantageous for reducing the content of W, Mo and Nb in high-purity tantalum powder products.

[0021] Optionally, the reducing agent is sodium.

[0022] Optionally, the tantalum-containing salt is potassium fluorotantalate.

[0023] In some embodiments, step 2) has one or more of the following features: - the pickling solution used in the first pickling contains 5-30% by weight of HNO3 and 0.5-5% by weight of HF; The pickling time is 1 to 5 hours.

[0024] In some embodiments, in step 4), the vacuum heat treatment is carried out using a heat treatment furnace that uses tantalum or tantalum alloy as a heating belt and heat shield, which is beneficial to avoid impurity contamination caused by the heat treatment furnace to the heat-treated tantalum powder.

[0025] In some embodiments, the vacuum heat treatment comprises, in sequence: A first temperature heat treatment, i.e., at a temperature of 800-1000 ° C for 0.5-3 hours; and The second temperature heat treatment is performed at a temperature of 1000 to 1550° C. for 0.5 to 3 hours.

[0026] In some embodiments, step 7) has one or more of the following features: - the pickling solution used in the second pickling contains 5-15 wt. % HNO3 and 0.2-2 wt. % HF; - Pickling time is 2 to 4 hours.

[0027] In some embodiments, after the first temperature heat treatment, the second temperature heat treatment is performed by increasing the temperature from the first temperature to the second temperature at a gradient of 5-20°C / min.

[0028] In some embodiments, step 5) has one or more of the following features: The temperature of the oxygen reduction heat treatment is 850 to 960°C; The time for the oxygen reduction heat treatment is 1 to 3 hours.

[0029] In some embodiments, the high purity tantalum powder has a Fisher grain size of 5.0 to 15.0 μm.

[0030] In some embodiments, the high purity tantalum powder has a bulk density of 2.6 to 6.0 g / cm 3 It is.

[0031] In a second aspect, the present application provides a method for producing a high purity tantalum target, comprising the steps of: - preparing a high purity tantalum powder according to the method of any one of claims 1 to 9; - smelting the high purity tantalum powder to form a high purity tantalum ingot; - processing the high purity tantalum ingot into a high purity tantalum target.

[0032] In some embodiments, the present application provides high purity tantalum powder.

[0033] In some embodiments, the high purity tantalum powder has a purity of 99.998% or greater.

[0034] In some embodiments, the high purity tantalum powder has an oxygen content of less than 600 ppm.

[0035] In some embodiments, the high purity tantalum powder has a total content of W, Mo, and Nb of less than 0.6 ppm.

[0036] In some embodiments, the high purity tantalum powder has a total content of W, Mo, and Nb of less than 0.4 ppm.

[0037] In some embodiments, the high purity tantalum powder has a total W and Mo content of less than 0.2 ppm.

[0038] In some embodiments, the high purity tantalum powder has a total W and Mo content of less than 0.1 ppm, and a Nb content of less than 0.4 ppm, preferably less than 0.3 ppm.

[0039] In some embodiments, the high purity tantalum powder has an O content of 390-510 ppm.

[0040] In some embodiments, the high purity tantalum powder has a C content of 7-8 ppm.

[0041] In some embodiments, the high purity tantalum powder has an N content of 20-49 ppm.

[0042] In some embodiments, the high purity tantalum powder has an Fe content of 2.49-8.04 ppm.

[0043] In some embodiments, the high purity tantalum powder has a Ni content of 1.21 to 2.85 ppm.

[0044] In some embodiments, the high purity tantalum powder has a Cr content of 1.34 to 2.67 ppm.

[0045] In some embodiments, the high purity tantalum powder has a K content of 0.42 to 1.19 ppm.

[0046] In some embodiments, the high purity tantalum powder has a Na content of 2.78 to 6.14 ppm.

[0047] In some embodiments, the high purity tantalum powder has a Si content of 0.91 to 4.16 ppm.

[0048] In some embodiments, the high purity tantalum powder has a W content of 0.016 to 0.057 ppm.

[0049] In some embodiments, the high purity tantalum powder has a Mo content of 0.034-0.035 ppm.

[0050] In some embodiments, the high purity tantalum powder has a Nb content of 0.087 to 0.22 ppm.

[0051] In some embodiments, the high purity tantalum powder has a Mg content of 0.53 to 0.94 ppm.

[0052] In some embodiments, the high purity tantalum powder has an O content of 510 ppm or less.

[0053] In some embodiments, the high purity tantalum powder has a C content of 8 ppm or less.

[0054] In some embodiments, the high purity tantalum powder has an N content of 49 ppm or less.

[0055] In some embodiments, the high purity tantalum powder has an Fe content of 8.04 ppm or less.

[0056] In some embodiments, the high purity tantalum powder has a Ni content of 2.85 ppm or less.

[0057] In some embodiments, the high purity tantalum powder has a Cr content of 2.67 ppm or less.

[0058] In some embodiments, the high purity tantalum powder has a K content of 1.19 ppm or less.

[0059] In some embodiments, the high purity tantalum powder has a Na content of 6.14 ppm or less.

[0060] In some embodiments, the high purity tantalum powder has a Si content of 4.16 ppm or less.

[0061] In some embodiments, the high purity tantalum powder has a W content of 0.057 ppm or less.

[0062] In some embodiments, the high purity tantalum powder has a Mo content of 0.035 ppm or less.

[0063] In some embodiments, the high purity tantalum powder has a Nb content of 0.22 ppm or less.

[0064] In some embodiments, the high purity tantalum powder has a Mg content of 0.94 ppm or less.

[0065] In some embodiments, the high purity tantalum powder is prepared by any one of the methods described above.

[0066] In some embodiments, the high purity tantalum powder has a Fisher grain size of 5.0 to 15.0 μm.

[0067] In some embodiments, the high purity tantalum powder has a bulk density of 2.6 to 6.0 g / cm 3 It is.

[0068] In some embodiments, the high purity tantalum powder refers to a tantalum powder having a total content of W, Mo, and Nb of less than 0.6 ppm, a Mg content of less than 1 ppm, and an oxygen content of less than 600 ppm.

[0069] High purity tantalum metal can be preferably prepared by reacting a tantalum-containing salt with at least one reducing agent (e.g., a compound or element) capable of reducing the tantalum-containing salt to tantalum metal while forming a second salt in a reaction vessel. The reaction vessel can be any vessel commonly used for metal reactions and must be capable of withstanding high temperatures of about 800°C to about 1200°C. For purposes of this application, the reaction vessel or its liner in which the tantalum-containing salt and the reducing agent capable of reducing the salt to tantalum come into contact are made of a material that has a vapor pressure at the melting point of tantalum that is equal to or higher than that of tantalum. The agitator in the reaction vessel may be made of the same material or may be lined with the same material. The liner may be present only on the portion of the reaction vessel and agitator in contact with the salt and tantalum. Examples of such metallic materials that can be used to construct the liner or reaction vessel include, but are not limited to, metal-based materials made from the following metals: nickel, chromium, iron, manganese, titanium, zirconium, hafnium, vanadium, ruthenium, cobalt, rhodium, palladium, platinum, or combinations or alloys thereof, as long as the vapor pressure of the alloy material at the melting point of tantalum is the same or higher than that of tantalum. Preferably, the metallic material is nickel or a nickel-based alloy, chromium or a chromium-based alloy, or iron or an iron-based alloy. If a liner is present on the reaction vessel and / or stirrer, its thickness is generally about 0.5 cm to about 3 cm. Liners of other thicknesses can also be used. Multi-layer liners made of the same or different metallic materials mentioned above are also within the scope of this application.

[0070] The tantalum-containing salt may be any salt capable of containing tantalum, such as potassium tantalum fluoride (potassium fluortantalate). The reducing agent capable of reducing the tantalum-containing salt to tantalum and a second salt in the reaction vessel may be any reducing agent capable of such reduction, and may be sufficient to reduce the tantalum-containing salt to tantalum metal and other components (e.g., salts) separable from the tantalum metal, such as salts that can be dissolved in water or other water sources. Preferably, the reducing agent is sodium. Typically, the second salt formed simultaneously with the reduction of the tantalum-containing salt is sodium fluoride. In this application, details of the reduction method applicable to this application are described in Kirk-Othmer, Encyclopedia of Chemical Engineering, Third Edition, Vol. 22, pages 541-564; U.S. Patent Nos. 2,950,185; 3,829,310; 4,149,876, and 3,767,456. Further details regarding tantalum processing methods can be found in U.S. Patent Nos. 5,234,491, 5,242,481, and 4,684,399. All of these patents and publications are incorporated herein by reference in their entirety.

[0071] Interpretation of terms: In this specification, the unit ppm means "ppm" by mass ratio, unless otherwise specified.

[0072] In one embodiment, the Fisher particle size (FSSS / μm) is determined according to the method specified in the standard "Method for determining the particle size of refractory metal and compound powders-Fisher method" (standard number GB / T3249-2009).

[0073] In one embodiment, the bulk density (SBD) is determined according to the method specified in the standard "Determination of bulk density of metal powders Part I Funnel method" (Standard No. GB / T1479.1-2011).

[0074] In one embodiment, O, N, and H in the tantalum powder are measured by the methods specified in "GB / T15076.13-2017 Tantalum Niobium Chemical Analysis Methods Part 13: Determination of Nitrogen Content by Inert Fusion Thermal Conductivity Method", "GB / T15076.4-2017 Tantalum Niobium Chemical Analysis Methods Part 14: Determination of Oxygen Content by Inert Fusion Infrared Absorption Method", and "GB / T15076.12-2017 Tantalum Niobium Chemical Analysis Methods Part 15: Determination of Hydrogen Content by Inert Fusion Thermal Conductivity Method", and other impurity elements are measured by the methods specified in "YS / T899-2013 High Purity Tantalum Chemical Analysis Method: Determination of Trace Quantitative Impurity Elements by Glow Discharge Mass Spectrometry".

[0075] In one embodiment, when the particle size of a powder is expressed by a mesh number, the symbol "+" or "-" before the mesh number indicates that the powder does not pass through or passes through the sieve of the mesh number, respectively. For example, "-100 mesh" means that the powder passes through a 100 mesh sieve, and "+150 mesh" means that the powder does not pass through a 150 mesh sieve. Thus, "-100 to +150 mesh" indicates that the powder passes through a 100 mesh sieve and does not pass through a 150 mesh sieve.

[0076] Beneficial Effects One or more technical solutions of the present disclosure have one or more of the following beneficial effects: (1) The tantalum powder of the present invention has high purity and low impurity content. (2) The method for producing tantalum powder according to the present application has the advantages of low cost, simple process, high efficiency, and easy mass production. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0077] Detailed Description of the Preferred Embodiments Hereinafter, the embodiments of the present application will be described in detail with reference to examples. However, it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and do not limit the scope of the present invention. In the examples, unless otherwise specified, the examples were carried out according to conventional conditions or conditions recommended by the manufacturer. All reagents and equipment used, unless the manufacturer is indicated, are conventional products available on the market.

[0078] Example 1 (1) Potassium fluorotantalate (with a total content of W, Mo, and Nb of less than 1.0 ppm) is reduced with a sufficient amount of sodium (purity ≥ 99.9%), and the reduced material is crushed to form a reduced material block of about 1 cm in size. The reduced material block is first leached in pure water for about 24 hours until the conductivity of the leaching solution is less than 500 us / cm, then pickled in a pickling solution containing 2.0 wt% HF and 15 wt% HNO3 with stirring for 3 hours, and then left for immersion for 1 hour. After that, it is repeatedly washed with pure water and suction filtered, and dried in a vacuum (120°C / 14 hours) to obtain tantalum raw material powder. The total content of W, Mo, and Nb in this tantalum raw material powder is 0.250 ppm.

[0079] (2) First milling (primary milling): The tantalum raw material powder was mixed with stainless steel balls having a diameter of approximately 20 mm in a mass ratio of 2:1, and the resulting mixture was added to a ball mill and ball milled for 40 minutes to obtain a primarily milled tantalum powder having a bulk density of 2.68 g / cc.

[0080] (3) The first pulverized tantalum powder was subjected to a first pickling (primary pickling) with stirring for 2 hours in a pickling solution containing 15 wt % HNO3 and 0.5 wt % HF, and then left to soak for 1 hour. Thereafter, it was repeatedly washed with pure water and suction filtered, and dried in a vacuum (120°C / 14 hours) to obtain a first pickled tantalum powder.

[0081] (4) The first pickled tantalum powder was placed in a vacuum heat treatment furnace using a heating belt and tantalum material as a heat shield, and vacuum heat treated at a temperature of 900°C for 1 hour. The temperature was then increased to 1200°C at a ramp rate of 15°C / min and maintained at this temperature for 2 hours, after which the powder was passivated and discharged from the furnace. It was then passed through a 50 mesh sieve to obtain heat-treated tantalum powder.

[0082] (5) The heat-treated tantalum powder was doped with magnesium powder at a doping amount of 1.0 wt%, placed in a heating furnace, the furnace was evacuated and filled with argon, heated to 930°C, and held at this temperature for 3 hours to carry out an oxygen reduction reaction. The furnace was then evacuated for 2 hours to remove the magnesium, after which the powder was passivated and discharged out of the furnace to obtain a powder with reduced oxygen.

[0083] (6) The oxygen-reduced powder was subjected to a second crushing (secondary crushing) using a crusher until it could pass through a 10 mesh sieve, to obtain a second crushed powder.

[0084] (7) The second crushed powder was subjected to a second pickling in a pickling solution containing 0.2 wt % HF and 15 wt % HNO3 with stirring for 2 hours, and then left to immerse for 1 hour to obtain a second pickled tantalum powder.

[0085] (8) The second pickled tantalum powder was repeatedly washed with pure water and suction filtered, vacuum dried (120°C / 14 hours), and passed through a 50 mesh sieve to obtain Sample 1. The chemical impurities and physical properties of the sample are shown in Table 1.

[0086] Example 2 (1) Potassium fluorotantalate (with a total content of W, Mo, and Nb of less than 1.0 ppm) is reduced with a sufficient amount of sodium (purity ≥ 99.9%), and the reduced material is crushed to a reduced material block of about 1 cm in size. The reduced material block is first leached in pure water for about 24 hours until the conductivity of the leaching solution is less than 500 us / cm, and then pickled with a pickling solution containing 2.0 wt% HF and 15 wt% HNO3 while stirring for 3 hours. After that, it is left for immersion for 1 hour, washed with pure water and suction filtered repeatedly, and vacuum dried (120°C / 14 hours) to obtain tantalum raw material powder. The total content of W, Mo, and Nb in the tantalum raw material powder was 0.200 ppm.

[0087] (2) The tantalum raw material powder was mixed with stainless steel balls having a diameter of about 15 mm in a mass ratio of 2:1, and the resulting mixture was added to a ball mill and ball milled for 40 minutes to obtain a powder having a bulk density of 3.0 g / cm 3 A first ground tantalum powder was obtained, which was

[0088] (3) The first crushed tantalum powder was first pickled (primary pickling) in a pickling solution containing 15% by weight HNO3 and 0.5% by weight HF for 2 hours while stirring, then immersed and left for 1 hour, then repeatedly washed with pure water, suction filtered, and vacuum dried (120°C / 14 hours) to obtain a first pickled tantalum powder.

[0089] (4) The first pickled tantalum powder was placed in a vacuum heat treatment furnace using tantalum material as a heating belt and heat shield, and subjected to vacuum heat treatment including the following steps: hold at 900°C for 1 hour, then ramp up the temperature to 1200°C at a rate of 15°C / min and maintain at this temperature for 2 hours, after which the powder was passivated and discharged from the furnace, followed by vacuum heat treatment, and passed through a 50 mesh sieve to obtain heat-treated tantalum powder.

[0090] (5) The heat-treated tantalum powder was doped with magnesium powder at a doping amount of 0.8 wt % and placed in a heating furnace, which was then evacuated and filled with argon, heated to 930°C, and held at this temperature for 3 hours to carry out an oxygen reduction reaction. The furnace was then evacuated for 2 hours to remove the magnesium, after which the powder was passivated and discharged out of the furnace to obtain a powder with reduced oxygen.

[0091] (6) The powder with reduced oxygen content was subjected to a second crushing (secondary crushing) using a crusher until it passed through a 10 mesh sieve, thereby obtaining a second crushed powder.

[0092] (7) The second crushed powder was subjected to a second pickling in a pickling solution containing 0.2 wt % HF and 15 wt % HNO3 with stirring for 2 hours, and then left to immerse for 1 hour to obtain a second pickled tantalum powder.

[0093] (8) The second pickled tantalum powder was repeatedly washed with pure water and suction filtered, vacuum dried (120°C / 14 hours), and passed through a 50 mesh sieve to obtain sample 2. The chemical impurities and physical properties of the sample are shown in Table 1.

[0094] Example 3 (1) Potassium fluorotantalate (with a total content of W, Mo, and Nb of less than 1.0 ppm) is reduced with a sufficient amount of sodium (purity ≥ 99.9%), and the reduced material is crushed to a reduced material block of about 1 cm in size. The reduced material block is first leached in pure water for about 24 hours until the conductivity of the leaching solution is less than 500 us / cm, and then pickled with a pickling solution containing 2.0 wt% HF and 15 wt% HNO3 while stirring for 3 hours. It is then left to soak for 1 hour, washed with pure water and suction filtered repeatedly, and dried in a vacuum (120°C / 14 hours) to obtain tantalum raw material powder. The total content of W, Mo, and Nb in this tantalum raw material powder was 0.160 ppm.

[0095] (2) The tantalum raw material powder was mixed with stainless steel balls having a diameter of about 15 mm in a mass ratio of 2:1, the resulting mixture was added to a ball mill and ball milled for 40 minutes to obtain a bulk density of 2.9 g / cm 3 A first ground tantalum powder was obtained, which was

[0096] (3) The first pulverized tantalum powder was subjected to a first pickling (primary pickling) in a pickling solution containing 15 wt % HNO3 and 0.5 wt % HF for 2 hours while stirring, and then left to stand for 1 hour for immersion. Thereafter, the powder was repeatedly washed with pure water, suction filtered, and vacuum dried (120°C / 14 hours) to obtain a first pickled tantalum powder.

[0097] (4) The first pickled tantalum powder was placed into a vacuum heat treatment furnace using tantalum material as a heating belt and heat shield, and subjected to vacuum heat treatment, including: holding at a temperature of 900°C for 1 hour, then increasing the temperature to 1250°C with a gradient of 15°C / min, and maintaining at this temperature for 2 hours, after which the powder was passivated and discharged from the furnace, and passed through a 50 mesh sieve to obtain heat-treated tantalum powder.

[0098] (5) The heat-treated tantalum powder was doped with magnesium powder at a doping amount of 0.7 wt%, then placed in a heating furnace, the inside of the furnace was evacuated and filled with argon, heated to 930°C, and held at this temperature for 3 hours to carry out an oxygen reduction reaction. The inside of the furnace was then evacuated for 2 hours to remove the magnesium, after which the powder was passivated and discharged out of the furnace to obtain a powder with reduced oxygen.

[0099] (6) The powder with reduced oxygen content was subjected to a second crushing (secondary crushing) using a crusher until it passed through a 10 mesh sieve, thereby obtaining a second crushed powder.

[0100] (7) The second crushed powder was subjected to a second pickling in a pickling solution containing 0.2 wt % HF and 15 wt % HNO3 with stirring for 2 hours, and then left to immerse for 1 hour to obtain a second pickled tantalum powder.

[0101] (8) The second pickled tantalum powder was repeatedly washed with pure water and suction filtered, vacuum dried (120°C / 14 hours), and passed through a 50 mesh sieve to obtain sample 3. The chemical impurities and physical properties of the sample are shown in Table 1.

[0102] Comparative Example 1 The process conditions of Comparative Example 4 were the same as those of Example 1, except that step (2) was not included.

[0103] Comparative Example 2 The process conditions of Comparative Example 4 were the same as those of Example 1, except that step (6) was not included.

[0104] Analysis and Judgment (1) The Fischer particle size (FSSS / μm) was determined according to the method specified in the standard “Method for determining particle size of refractory metal and compound powders - Fischer method” (standard number GB / T3249-2009).

[0105] (2) The bulk density (SBD) was measured in accordance with the method specified in the standard "Determination of bulk density of metal powders Part I Funnel method" (Standard No. GB / T1479.1-2011).

[0106] (3) The O, N, and H in the tantalum powder were measured in accordance with the methods specified in the Chinese national standards "GB / T15076.13-2017 Tantalum and niobium chemical analysis methods Part 13: Determination of nitrogen content by inert melt thermal conductivity method," "GB / T15076.4-2017 Tantalum and niobium chemical analysis methods Part 14: Determination of oxygen content by inert melt infrared absorption method," and "GB / T15076.12-2017 Tantalum and niobium chemical analysis methods Part 15: Determination of hydrogen content by inert melt thermal conductivity method." The amounts of other impurity elements were determined in accordance with the method specified in "YS / T899-2013 High-purity Tantalum Chemical Analysis Methods: Determination of Trace Impurity Elements by Glow Discharge Mass Spectrometry."

[0107] The chemical impurities and physical properties of the samples are shown in Table 1.

[0108] [Table 1]

[0109] From the above data, it can be seen that the high purity tantalum powder obtained by the method of the present application has a total content of refractory impurities W, Mo and Nb of less than 0.6 ppm, a Mg content of less than 1 ppm, and an oxygen content of less than 600 ppm, which can meet the use requirements of high purity tantalum products.

[0110] As can be seen by comparing Examples 1 to 3 with Comparative Example 1, in Examples 1 to 3, the first pulverization operation in step (2) and the second pulverization operation in step (6) are very important. The first pulverization operation reduces the bulk density to 2.6 to 6 g / cm. 3 The first crushed tantalum powder is obtained, and the first pickling effectively removes impurity elements in the first crushed tantalum powder. The second crushing obtains tantalum powder that can pass through a 10 mesh sieve, and the second pickling effectively removes impurity elements, particularly magnesium element, in the second crushed tantalum powder. The combination of the above features effectively improves the purity of the high purity tantalum powder of Examples 1 to 3, and the obtained high purity tantalum powder has a total content of W, Mo and Nb of less than 0.6 ppm and a Mg content of less than 1 ppm.

[0111] The tantalum powder obtained in Comparative Example 1 contains W, Mo, and Nb in a total content of up to 0.7 ppm because the first crushing operation was omitted.

[0112] The tantalum powder obtained in Comparative Example 2, in which the second pulverization operation was not carried out, had a Mg content of 4.9 ppm.

[0113] Although the specific embodiments of the present disclosure have been described in detail, it will be understood by those skilled in the art that, according to all the teachings disclosed, various changes can be made to the details, and all of these changes are within the scope of protection of the present disclosure. The full scope of the present disclosure is given by the appended claims and their equivalents.

Claims

1. 1. A method for preparing a high-purity tantalum powder, the high-purity tantalum powder having a total content of W, Mo, and Nb of less than 0.6 ppm, a magnesium content of less than 1 ppm, and an oxygen content of less than 600 ppm, the method comprising the steps of: 1) preparing a tantalum raw material powder having a total content of W, Mo, and Nb of less than 0.6 ppm; 2) A first pulverization is performed on the tantalum raw material powder to obtain a powder having a particle size of 2.6 g / cm 3 obtaining a first milled tantalum powder having a bulk density greater than 3) performing a first pickling on the first ground tantalum powder to obtain a first pickled tantalum powder; 4) subjecting the first pickled tantalum powder to a vacuum heat treatment, and passivating the tantalum powder after the vacuum heat treatment to obtain a passivated tantalum powder; 5) doping the passivated tantalum powder with a metal reducing agent, performing an oxygen reduction heat treatment, passivating the powder, and discharging the passivated powder out of the furnace to obtain an oxygen-reduced powder; 6) performing a second grinding on the oxygen-reduced powder until the powder passes through a 5-15 mesh sieve to obtain a second ground powder; 7) performing a second pickling on the second ground powder to obtain a second pickled tantalum powder; 8) washing and drying the second pickled tantalum powder;

2. The method further includes a step of reducing the tantalum-containing salt with a reducing agent to obtain a tantalum raw material powder, wherein (1) the purity of the reducing agent is 99.9% or more; (2) The total content of W, Mo and Nb in the tantalum-containing salt is less than 1 ppm; Optionally, the reducing agent is sodium; Optionally, the tantalum-containing salt is potassium fluorotantalate.

3. The step 3) has the following characteristics: The pickling solution used in the first pickling is 5-30% by weight HNO 3 and 0.5 to 5 wt. % HF; The method for preparing tantalum powder according to claim 1, characterized in that it comprises one or more of the following: - the pickling time is 1 to 5 hours.

4. 2. The method for preparing tantalum powder according to claim 1, wherein in step 4), the vacuum heat treatment is carried out using a heat treatment furnace using tantalum or a tantalum alloy as a heating belt and a heat shield.

5. The vacuum heat treatment is performed at a first temperature of 800 to 1000° C. for 0.5 to 3 hours.

2. The method for preparing tantalum powder according to claim 1, further comprising the step of: (a) heat treating the tantalum powder at a temperature of 1000 to 1550° C. for 0.5 to 3 hours;

6. The step 7) has the following characteristics: The pickling solution used in the second pickling contains 5 to 15% by weight of HNO 3 and 0.2 to 2 wt. % HF; The method for preparing tantalum powder according to claim 1, characterized in that it has one or more of the following characteristics: - the pickling time is 2 to 4 hours.

7. 2. The method for preparing tantalum powder according to claim 1, characterized in that after the first temperature heat treatment, a second temperature heat treatment is performed by increasing the temperature from the first temperature to the second temperature at a gradient of 5 to 20° C. / min.

8. Step 5) has the following characteristics: The temperature of the oxygen reduction heat treatment is 850 to 960°C.

2. The method for preparing tantalum powder according to claim 1, wherein the oxygen reduction heat treatment time is 1 to 3 hours.

9. 2. The method of claim 1, characterized in that it has one or more of the following characteristics: the high purity tantalum powder has a Fischer grain size of 5.0 to 15.0 μm. The high purity tantalum powder has a density of 2.6 to 6.0 g / cm 3 It has a bulk density of

10. - preparing a high purity tantalum powder according to the method of any one of claims 1 to 9, - smelting the high purity tantalum powder into high purity tantalum ingots; - processing the high purity tantalum ingot into a high purity tantalum target.

11. A high purity tantalum powder prepared according to the method of any one of claims 1 to 9.

12. The oxygen content is less than 600 ppm, the sum of the contents of W, Mo, and Nb is less than 0.6 ppm, and the sum of the contents of W and Mo is less than 0.2 ppm; Optionally, the high purity tantalum powder has a purity of 99.998% or more, characterized in that the high purity tantalum powder is prepared according to the method according to any one of claims 1 to 9.

13. 13. The high purity tantalum powder of claim 12, having one or more of the following characteristics: - The high purity tantalum powder has a Fischer particle size of 5.0 to 15.0 μm. - High purity tantalum powder is 2.6 to 6.0 g / cm 3 It has a bulk density of

Citation Information

Patent Citations

  • Method for purifying tantalum powder and tantalum target

    CN102517460A

  • High-purity tantalum ingot and preparation method thereof

    CN111893325A

  • Niobium or tantalum powder, its manufacturing method, and solid electrolytic capacitor

    JP2001345238A

  • High-purity tantalum powder and its preparation method

    JP2017512897A

  • Tantalum sputtering target and method of manufacture

    US20020132388A1